Green Breaks: The Restorative Effect of the School Environment’s Green Areas on Children’s Cognitive Performance - Amicone, Giulia; Petruccelli, Irene; De Dominicis, Stefano; Gherardini, Alessandra; Costantino, Valentina; Perucchini, Paola; Bonaiuto, Marino (Frontiers in Psychology, 2018)
Restoration involves individuals’ physical, psychological and social resources, diminished by meeting demands of everyday life. Psychological restoration can be provided by specific environments, in particular by natural environments. Research reports a restorative effect of nature on human beings, specifically in terms of the psychological recovery from attention fatigue and restored mental resources previously spent in activities that require attention. Two field studies in two Italian primary schools tested the hypothesized positive effect of recess-time spent in a natural (vs. built) environment on pupils’ cognitive performance and their perceived restorativeness, using standardized tests. In Study 1, children’s psychological restoration was assessed measuring sustained and selective attention, working memory, and impulse’ control, before and after morning recess-time. Team standardized play-time was conducted in a natural (vs. built) environment, measuring perceived restorativeness after each recess-time. Results showed a greater increase in sustained and selective attention, concentration, and perceived restorativeness from pre-test to post-test after the Natural Environment condition. In Study 2 the positive effect of free-play recess-time in a natural (vs. built) environment was assessed during the afternoon school-time on sustained and selective attention and perceived restorativeness. Results showed an increase of sustained and selective attention after the Natural Environment condition (vs. Built) and a decrease after the built environment break. Higher scores in perceived restorativeness were registered after the Natural (vs. Built) Environment condition. Team standardized and individual free-play recess in a natural environment (vs. built) support pupils’ attention restoration during both morning and afternoon school-time, as well as their perceived restorativeness of recess environment. Theoretical and practical implications are discussed in terms of nature’s role both for school ground design or re-design, and for school’s activities organization.